Exploring molecular docking with E-pharmacophore and QSAR models to predict potent inhibitors of 14-α-demethylase protease from Moringa spp - Damilola Alex Omoboyowa (Elsevier, 2022)
Chagas disease is a neglected tropical disease (NTD) caused by Trypanosoma cruzi, this protozoan is transmitted by kissing bug. Two nitroheterocyclic drugs available for the treatment of chagas disease are not only resistance but also parade toxicity effect. Therefore, this study investigates the inhibitory activity of bioactive compounds from Moringa spp against 14-α-demethylase protease of T. cruzi through e-pharmacophore and QSAR models with molecular docking and pharmacokinetic studies using Schrödinger suite. The density functional theory (DFT) of the lead compounds was performed by Spatan 10. From the pharmacophore model and ADME analysis, eight active molecules were obtained which showed high binding affinity and better interaction with the target compared with the reference ligand (Benznidazole). AutoQSAR was employed to build a model for the prediction of the compounds bioactivities with the eight compounds showing better inhibitory pIC50 comparable with the reference ligand against 14-α-demethylase protease. The results of the frontier molecular orbitals of the lead molecules revealed that the EHOMO values of the lead compounds range from -6.70 to -5.41 eV predicting the lead compounds as electron donator. Overall, this study predicted isorhamnetin, kaemferide, rhamnetin, niaziminin, aurantiamide acetate, niazirinin, eugenol and sinapic acid as inhibitors of 14-α-demethylase protease. Hence, further in vitro and in vivo experiments are suggested to ascertain the therapeutic potential of these compounds in the treatment of chagas disease.